2020
DOI: 10.5812/ijp.95074
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Abdominal Massage on the Feeding Tolerance of Neonates with Very Low Birth Weight

Abstract: Background: Functional immaturity of the gastrointestinal tract in premature infants can cause several problems, leading to feeding intolerance.Objectives: This study aimed to investigate the effect of abdominal massage on the feeding tolerance of neonates with very low birth weight. Methods: This randomized single-blind clinical open-label trial was conducted on low-birth-weight neonates, who were hospitalized in the neonatal intensive care units (NICUs) of two tertiary university hospitals from March 2016 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…These results are similar to those in the study performed by Ardiansyah et al. ( 2020 ) and Haghshenas et al ( 2020 ), who revealed that the abdominal massage had a positive effect on the incidence of feeding intolerance in premature infants. In addition, Mojaveri et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are similar to those in the study performed by Ardiansyah et al. ( 2020 ) and Haghshenas et al ( 2020 ), who revealed that the abdominal massage had a positive effect on the incidence of feeding intolerance in premature infants. In addition, Mojaveri et al.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, regarding feeding tolerance, the current results demonstrated that there was a slight significant improvement in all items of feeding tolerance for the study group after abdominal massage, and there was also a slight significant difference between the study and control groups at the fourth day after abdominal massage related to all items of feeding tolerance such as frequency of defe- 2020), who revealed that the abdominal massage had a positive effect on the incidence of feeding intolerance in premature infants. In addition, Mojaveri et al (2020) reported that abdominal massage, which leads to less distension and GRV, is recommended before enteral feeding for very LBW infants and Jin et al (2020) showed that intervention with abdominal massage might promote weight gain and improve feeding tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these advantages, abdomen massage is highlighted as a helpful nursing care strategy in the NICU context (Lu et al, 2020). This in turn leads to alleviating abdominal distension as highlighted in a study done by (Haghshenas et al, 2020), who reported a substantial change in abdominal circumference within the massage group.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding intolerance is defined as a delay in gastric emptying and the presence of a residual volume of previous nutrition in the stomach of more than 50% (1,2). Feeding intolerance is a common clinical problem among preterm infants with an overall prevalence of 27% (15 -30%) (3), and in most cases, it indicates a benign condition related to gastrointestinal motility dysfunction due to immaturity of the intestine with delayed meconium passage, although it can be an early sign of necrotizing enterocolitis (NEC), sepsis, or other serious gastrointestinal problems (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%